1983
DOI: 10.4141/cjas83-054
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Sugar Cane Final Molasses by the Pig: Energy Metabolism

Abstract: A. 1983portions being offered at 0800 h and 1600 h. In each batch, two pigs were allocated to the starch diet and three each to the molasses and sugar diets. After the pigs had been consuming the diets for 10 days they were transferred to cages which allowed separation and collection of feces and urine. The pigs remained in the cages for l0 days, with feces and urine being collected for the last 7 days. The feces were collected at 0800, 1200, 1600, and 2000 h and frozen. The urine was stored at 4'C. At the end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
4

Year Published

1990
1990
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 6 publications
2
5
0
4
Order By: Relevance
“…The energy DC (83.6%) is similar to the value reported in the French tables (85%; Sauvant et al, 2002). The DE values of molasses (13.1 MJ/kg DM) are in accordance with Bayley et al (1983) study (13.6 MJ/kg DM) and with French (Sauvant et al, 2002;12.7 MJ/kg DM) and Brazilian (Rostagno, 2005;13.5 MJ/kg DM) feeding tables.…”
Section: Nutritional and Energy Values Of Final Sc Molassessupporting
confidence: 65%
See 3 more Smart Citations
“…The energy DC (83.6%) is similar to the value reported in the French tables (85%; Sauvant et al, 2002). The DE values of molasses (13.1 MJ/kg DM) are in accordance with Bayley et al (1983) study (13.6 MJ/kg DM) and with French (Sauvant et al, 2002;12.7 MJ/kg DM) and Brazilian (Rostagno, 2005;13.5 MJ/kg DM) feeding tables.…”
Section: Nutritional and Energy Values Of Final Sc Molassessupporting
confidence: 65%
“…Bayley et al (1983) showed that the range for ash and soluble sugars contents in Cuban commercial conditions was from 5.7 to 16.3 g/100 DM and from 46 to 76 g/100 DM, respectively. In our study, the SC molasses contained 15.1 g/100 g DM of ash and 71.0 g/100 g DM of soluble sugars (sucrose, fructose and glucose).…”
Section: Nutritional and Energy Values Of Final Sc Molassesmentioning
confidence: 99%
See 2 more Smart Citations
“…Por otra parte, existen estudios de producción de alimentos balanceados ricos en proteínas a partir de los residuos del proceso de producción de azúcar, como fuente alternativa de obtención de proteína (Leme et al, 2003;Ferrer et al, 2004). Un ejemplo de interés es el caso de la explotación porcina y su limitante en los países tropicales, debido a los altos costos de una alimentación basada en granos de cereales lo cual no es sostenible ni apropiada y disminuyen la rentabilidad de la industria; por lo que la alternativa está en el desarrollo de tecnologías que permitan utilizar los recursos disponibles en el trópico para la alimentación de cerdos en sus diferentes etapas (Bayley et al, 1983;Figueroa, 1989;Figueroa et al, 1993). Además, el uso de bagazo y subproductos del procesamiento de la caña de azúcar, como es el caso de las melazas, están siendo utilizados como sustrato en procesos biotecnológicos (Martínez et al, 2002;Silva, et al, 2006;.…”
Section: Posibilidades De Uso De Los Residuos De La Agroindustria Azuunclassified